El acompañamiento de los padres en el rendimiento académico con los niños de tercer año de educación básica unidad educativa ”Camilo Gallegos” periodo 2017 – 2018 - Inga Gualpa, Mónica Alexandra (2018)
Research whose main objective is to analyze the accompaniment of parents in the school performance of children of the third year of Basic Education of the Camilo Gallegos Educational Unit, Academic Period 2017-2018, with a population of 39 children, non-experimental research since in the research process none of the variables were manipulated, that is to say; the problem investigated was studied as it occurred in its context, with the reason of identifying the causes of the low school performance of children, verifying the importance of the accompaniment of parents in carrying out their children's school tasks, with a type of documentary, field and descriptive research in order to identify the causes and effects of the given problem; Through the technique of observation, the investigated object was directly captured, with the support of observation cards as a tool, which allowed the study and analysis of the results obtained, reaching the conclusion that the accompaniment of parents in the academic performance of The third year of Basic education is of vital importance since it allows the good development both in the learning and in their professional and personal life, achieving the reinforcement of their knowledge with the support of their parents that helps them to be more secure to potentialize their intellectual abilities, creating in them an environment of security, forging them responsible and original, promoting their integral development